The therapeutic effect and mechanism of parthenolide in skeletal disease, cancers, and cytokine storm - Zhu, Sipin; Sun, Ping; Bennett, Samuel; Charlesworth, Oscar; Tan, Renxiang; Peng, Xing; Gu, Qiang; Kujan, Omar; Xu, Jiake (Frontiers in Pharmacology, 2023)
Parthenolide (PTL) was first isolated from Magnolia grandiflora and identified as a small molecule inhibitor of cancer. PTL has the chemical structure of C15H20O3 with characteristics of sesquiterpene lactones and exhibits the biological property of inhibiting DNA biosynthesis of cancer cells. In this review, we summarise recent progress of research of medicinal PTL, including the therapeutic effects on skeletal diseases, cancers, and inflammation-induced cytokine storm. Mechanistic investigations reveal that PTL predominantly inhibits NF-κB activation and other signalling pathways such as reactive oxygen species. As an inhibitor of NF-κB, PTL appears to inhibit several cytokines, including RANKL, TNF-a, IL1b, together with LPS induced activation of NF-kB and NF-kB-mediated specific gene expression. It is also proposed that PTL could inhibit cytokine storms or hypercytokinemia triggered by COVID-19 via blocking the activation NF-κB signalling. Understanding the pharmacologic properties of PTL will assist us to develop its therapeutic application for medical conditions including arthritis, osteolysis, periodontal disease, cancers, and COVID-19 related disease.